2015
DOI: 10.1126/science.aac5992
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of in vivo fitness and diet responsiveness in multiple human gut Bacteroides

Abstract: Libraries of tens of thousands of transposon mutants generated from each of four human gut Bacteroides strains, two representing the same species, were introduced simultaneously into gnotobiotic mice together with 11 other wild-type strains to generate a 15-member artificial human gut microbiota. Mice received one of two distinct diets monotonously, or both in ordered sequence. Quantifying the abundance of mutants in different diet contexts allowed gene-level characterization of fitness determinants, niche, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
223
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(237 citation statements)
references
References 44 publications
5
223
0
Order By: Relevance
“…These results highlight the importance of dietary macronutrients and exercise on positively shaping the gut microbiota composition. Fascinating discoveries have been made from the recently development multi-taxon Insertion Sequencing (INSeq) method, which monitors the genetic factors that enable members of the gut microbial community to flourish within this niche 75. This approach can be used to understand the mechanisms (gene-level characterisation) that determine gut microbial fitness and perturbation through diet, disease and clinical treatment.…”
Section: Diet and Obesitymentioning
confidence: 99%
“…These results highlight the importance of dietary macronutrients and exercise on positively shaping the gut microbiota composition. Fascinating discoveries have been made from the recently development multi-taxon Insertion Sequencing (INSeq) method, which monitors the genetic factors that enable members of the gut microbial community to flourish within this niche 75. This approach can be used to understand the mechanisms (gene-level characterisation) that determine gut microbial fitness and perturbation through diet, disease and clinical treatment.…”
Section: Diet and Obesitymentioning
confidence: 99%
“…In this study, protein consumption was associated with elevated microbial diversity (across 22 phyla), and athletes with a lower BMI had higher levels of Akkermansia , which has been inversely correlated with obesity in both mice [33] and humans [34] . Finally, a recent animal study has found, using a novel approach (multi-taxon insertion sequencing method), that the host genotype may influence dietmicrobiome interactions [35] .…”
Section: The Gut Microbiotamentioning
confidence: 99%
“…Additionally, studies of the human gut microbiome have identified GH43 enzymes to be among the most abundant CAZymes present (16,17). Such abundance in both cases suggests an important role in accessing a wide range of complex substrates and highlights the need for accurate functional predictions for GH43 enzymes in genomic and metagenomic studies.…”
mentioning
confidence: 99%
“…The family is dominated by bacterial sequences (4,197), with eukaryotic (312) and archaeal (17) sequences also contained in the group. The functional characteristics of this family have been studied comparatively well, with 146 members that have been characterized biochemically against a natural or synthetic substrate, but this analysis still lags far behind the deposition of new sequences.…”
mentioning
confidence: 99%